2008
DOI: 10.1140/epjc/s10052-008-0600-z
|View full text |Cite
|
Sign up to set email alerts
|

The use of quantum-correlated D0 decays for φ3 measurement

Abstract: Abstract. We report the results of the Monte Carlo study of the method to determine the CKM angle φ 3 using Dalitz plot analysis of D 0 produced in B ± → DK ± decay. Our main goal is to find the optimal strategy for a model-independent φ 3 extraction. We find that the analysis using decays of CP-tagged D mesons only cannot provide a completely model-independent measurement in the case of a limited data sample. The procedure involving binned analysis of B ± → DK ± and ψ(3770)D decays is proposed which, in contr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
137
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(137 citation statements)
references
References 16 publications
0
137
0
Order By: Relevance
“…(41) Since D decays do not violate CP one can relate c i and s i in i th bin with the CP conjugated one,ī, hence cī = c i , and sī = −s i . A MC based feasibility study showed that the optimal strategy using this model independent approach is statistically only 30% worse than the model dependent method [208,209]. The prior measurement of c i , and s i at charm factory (or at SuperB via running at charm threshold) is a crucial ingredient to measure γ in this way.…”
Section: Tests Of Cp Tmentioning
confidence: 99%
“…(41) Since D decays do not violate CP one can relate c i and s i in i th bin with the CP conjugated one,ī, hence cī = c i , and sī = −s i . A MC based feasibility study showed that the optimal strategy using this model independent approach is statistically only 30% worse than the model dependent method [208,209]. The prior measurement of c i , and s i at charm factory (or at SuperB via running at charm threshold) is a crucial ingredient to measure γ in this way.…”
Section: Tests Of Cp Tmentioning
confidence: 99%
“…For a quasi-CP tag, the c i sensitive term is scaled by (2F + − 1) rather than 1. For the tag modes K 0 S,L π + π − [11,12], the double-tagged yield is…”
Section: Jhep01(2018)082mentioning
confidence: 99%
“…However, to better exploit the information available in multi-body D decays, the phase space can be divided into bins such that regions of constructive and destructive interference do not dilute each other. Such a method has already been applied to the K 0 S π + π − final state [21] which gives the best single measurement of γ to date [22]; here an amplitude-model was used to group regions of phase space that have a similar phase difference between D 0 → K 0 S π + π − and D 0 → K 0 S π + π − amplitudes [23]. Recently an amplitude model for D → 4π ± has become available [24], so in this paper a similar technique is applied to the 4π ± final state.…”
Section: Jhep01(2018)144mentioning
confidence: 99%
“…To determine how sensitive a binning scheme is to a measurement of γ, the Q ± values are defined [23], 8) where N i B ± is the number of B ± → DK ± , D → f decays expected in bin i (eq. (2.11) and eq.…”
Section: Optimal Binningmentioning
confidence: 99%